2011
DOI: 10.1016/j.neuron.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

RIM Proteins Activate Vesicle Priming by Reversing Autoinhibitory Homodimerization of Munc13

Abstract: At a synapse, the presynaptic active zone mediates synaptic vesicle exocytosis. RIM proteins are active-zone scaffolding molecules that – among others – mediate vesicle priming, and directly or indirectly interact with most other essential presynaptic proteins. In particular, the Zn2+-finger domain of RIMs binds to the C2A-domain of the priming factor Munc13, which forms a homodimer in the absence of RIM, but a heterodimer with it. Here we show that RIMs mediate vesicle priming not by coupling Munc13 to other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
343
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 266 publications
(370 citation statements)
references
References 56 publications
23
343
0
4
Order By: Relevance
“…In RIM1/2 double-deficient neurons, the RRP is massively decreased because RIM proteins mediate synaptic vesicle priming by disinhibiting inactive Munc13 homodimers (14,19,29). We here found that similar to evoked IPSCs and spontaneous release, deletion of individual RIM genes decreased the RRP size (Fig.…”
Section: Role Of Rim Proteins In Different Forms Of Evoked and Spontasupporting
confidence: 51%
See 3 more Smart Citations
“…In RIM1/2 double-deficient neurons, the RRP is massively decreased because RIM proteins mediate synaptic vesicle priming by disinhibiting inactive Munc13 homodimers (14,19,29). We here found that similar to evoked IPSCs and spontaneous release, deletion of individual RIM genes decreased the RRP size (Fig.…”
Section: Role Of Rim Proteins In Different Forms Of Evoked and Spontasupporting
confidence: 51%
“…We here found that similar to evoked IPSCs and spontaneous release, deletion of individual RIM genes decreased the RRP size (Fig. S4), although the size of the decrease is less than that observed with the double deletion (14,19,29). This experiment suggests that RIM1 and RIM2 promote priming in an additive fashion and cannot compensate in priming for each other's loss.…”
Section: Role Of Rim Proteins In Different Forms Of Evoked and Spontamentioning
confidence: 51%
See 2 more Smart Citations
“…The present study and previous reports by Wadel et al (3) and Müller et al (7) show that primed SVs just recruited from SRP after a predepolarization are somewhat less Ca 2+ -sensitive than FRP SVs at steady state. Recently, it has been shown that activation of Munc13 requires its interaction with RIM, which renders the MUN domain of Munc13 to be exposed (23,24). Rab3-interacting molecule (RIM) interacts with Ca 2+ channels, and thus may be closely associated with them in the active zone.…”
Section: Discussionmentioning
confidence: 99%